Air pollution in Northeast Asia: can framing of public messages influence beliefs and attributions?. Issue 1 (2nd January 2022) - Shapiro, Matthew A.; Bolsen, Toby; Kim, Yungwook
ABSTRACT: Public support for any policy is often influenced by communications highlighting aspects of it – such as a policy's perceived "costs" or "benefits" to people. This paper tests for these attitudinal differences as they relate to the transboundary air pollution problem in South Korea where cross-national coordination efforts among China, South Korea, and Japan have done little to alleviate the problem. We conduct an emphasis framing experiment launched in mid-2019, testing whether the importance of cooperation with China decreases or increases with exposure to different frames, such as Korea working alone to address the problem or Korea and China working together. While the message frames utilised in our study did not show a powerful direct impact on respondents, a secondary analysis reveals differences across pre-existing beliefs and attitudes. For Korean policy makers to effectively respond to both domestic and foreign demands related to the air pollution problem in Northeast Asia, there must be acknowledgement of this variance throughout the policy making process. This study thus highlights a tension for policy makers: trying to shift public beliefs through specific messages or allowing change in policy design by engaging the public in a more bottom-up deliberative approach.